2016
DOI: 10.1371/journal.pone.0168192
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Biological Evaluation of Anti-HER2 Indocyanine Green-Encapsulated PEG-Coated PLGA Nanoparticles for Targeted Phototherapy of Breast Cancer Cells

Abstract: Human epidermal growth factor receptor 2 (HER2)-overexpressed breast cancer is known to be more aggressive and resistant to medicinal treatment and therefore to whom an alternative therapeutics is needed. Indocyanine green (ICG) has been widely exploited in breast cancer phototherapy. However, drawbacks of accelerated degradation and short half-life (2–4 min) in blood seriously hamper its use in the clinic. To overcome these challenges, an anti-HER2 ICG-encapsulated polyethylene glycol-coated poly(lactic-co-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…We believe that the temperature increase is one of the main factors in the antitumor effects obtained in our study, because it was previously reported that PDT using ICG also had a thermal effect [ 29 ]. It seems likely that the temperature increase by PDT depends on a variety of photosensitizers including ICG.…”
Section: Discussionmentioning
confidence: 81%
“…We believe that the temperature increase is one of the main factors in the antitumor effects obtained in our study, because it was previously reported that PDT using ICG also had a thermal effect [ 29 ]. It seems likely that the temperature increase by PDT depends on a variety of photosensitizers including ICG.…”
Section: Discussionmentioning
confidence: 81%
“…Properties such as low toxicity, high water solubility, and high NIR absorptivity have made ICG and its derivatives a popular choice for PAT and medical diagnosis [ 38 , 96 ]. ICG has been used in fusion with different targeting affibodies to label cancer biomarkers such as HER2 [ 97 ] and B7-H3 [ 59 ] for early-cancer imaging with photodynamic therapy (PDT) capability. Strategies such as PEG conjugation and micellar formation have been employed to enhance the permeability and retention of ICG via the EPR effect.…”
Section: Exogenous Contrast Agentsmentioning
confidence: 99%
“…Recently, GBNs have been widely reported to have antibacterial activity with their sharp edges to bacterial membranes leading to the destruction of lipid biomolecules and oxidative stress [ 121 ]. Zhao et al speculated that [ 68 ] the antibacterial activity of GBNs is bacterial species dependent rather than gram dependent [ 122 ]. The antibacterial activity of GBNs involves several mechanisms together than an individual mechanism responsible for antibacterial activity (Table 3 and Fig.…”
Section: Biomedical Applications In Therapeutics Of Gbnsmentioning
confidence: 99%
“…The other techniques such as fluorescence spectroscopy, surface plasmon resonance (SPR) and surface-enhanced Raman scattering (SERS) have also shown promising results in the detection of biosensors. Compared to conventional methods, the biosensors are enabled to quantitatively detect small molecules to large biomolecules [ 68 ]. Among GBNs, GO exhibits characteristic G-band in Raman spectra along with its water solubility and biocompatibility.…”
Section: Biomedical Applications Of Gbns In Engineeringmentioning
confidence: 99%
See 1 more Smart Citation